Isolation and identification of lactobacilli from traditional yogurts as potential starter cultures. (August 2021) - Celik, Omer F.; Con, Ahmet H.; Saygin, Hayrettin; Şahin, Nevzat; Temiz, Hasan
Abstract: Potential lactobacilli isolates (20) from traditional yogurt samples were primarily selected based on their antimicrobial activity against common pathogens of Escherichia coli and Staphylococcus aureus . Following this, the highest acidity values were determined in K1 (0.63%) and EPSC2 (0.61%) isolates after 6 h; KKC1 (1.62%) and EPSC2 (1.59%) after 24 h. The highest proteolytic activity in the first 36 h of incubation was observed in K11B, M2, CBB5 and CBB3 isolates while the lowest activity was in K10, M6, and KKC2 isolates, respectively. Subsequently, 10 isolates that carry the potential to be used as yogurt starter cultures were picked and identified at the molecular level using 16S rDNA sequences and a phylogenetic tree was created. The closest species to all of the selected isolates was determined to be Lactobacillus bulgaricus . The flavor profiles of these isolates indicated that the highest acetaldehyde concentrations were detected in the KKC1, M6, and KKC2 isolates while these values were found to be higher than that of the commercial Lactobacillus. Consequently, CBX, CBH4, M6, EPSC2, and KKC2 were found to possess the potential to be used as starter cultures therefore they could be recommended for utilization in fermented dairy products, especially yogurt. Highlights: Lactobacilli with antimicrobial activity were isolated from traditional yogurt samples. The closest species to all isolates was assigned as Lactobacillus bulgaricus . KKC1, M6, and KKC2 were better producers of acetaldehyde than the commercial strain. CBX, CBH4, M6, EPSC2, and KKC2 are recommended as potential yogurt starters.